1997
DOI: 10.1002/(sici)1097-0010(199707)74:3<281::aid-jsfa794>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Organically and Conventionally Grown Foods—Results of a Review of the Relevant Literature

Abstract: This review is concerned with the summary and evaluation of the results from more than 150 investigations comparing the quality of conventionally and organically produced food or of foods produced with the aid of di †erent fertilisation systems. Cereals, potatoes, vegetables, fruits, wine, beer, bread, cakes and pastries, milk, meat, eggs and honey, as well as products made from them, have been included in the review. Most of the studies evaluated are physicochemical investigations of concentrations of desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
419
4
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(458 citation statements)
references
References 6 publications
20
419
4
15
Order By: Relevance
“…Certain studies have scientifically proven the benefits of organic products regarding lower content in synthetic agrochemicals (Poulsen & Andersen, 2003;Andersen, & Poulsen, 2001), nitrate and nitrite (De Martin & Restani, 2003), and drug residues (Cabaret, Mage, & Bouilhol, 2002;Carstensen, Vaarts, & Roepstorff, 2002), however a lack of differentiation in metal elements has also been demonstrated (Magkos, Arvaniti, & Zampelas, 2006). Thus, the organically produced vegetables exhibited no significant differences in relation to the levels of heavy metals from conventional production (Ghidini et al, 2005;Woese, Lange, Boess, & Werner-Bögl, 1997). Nevertheless, other authors showed marked differences against organic production.…”
Section: Influence Of Cereal Production Methods On Lead and Cadmium Comentioning
confidence: 99%
“…Certain studies have scientifically proven the benefits of organic products regarding lower content in synthetic agrochemicals (Poulsen & Andersen, 2003;Andersen, & Poulsen, 2001), nitrate and nitrite (De Martin & Restani, 2003), and drug residues (Cabaret, Mage, & Bouilhol, 2002;Carstensen, Vaarts, & Roepstorff, 2002), however a lack of differentiation in metal elements has also been demonstrated (Magkos, Arvaniti, & Zampelas, 2006). Thus, the organically produced vegetables exhibited no significant differences in relation to the levels of heavy metals from conventional production (Ghidini et al, 2005;Woese, Lange, Boess, & Werner-Bögl, 1997). Nevertheless, other authors showed marked differences against organic production.…”
Section: Influence Of Cereal Production Methods On Lead and Cadmium Comentioning
confidence: 99%
“…As a result the interest in organic agriculture and environmentally-friendly agricultural products is increasing, and in particular consumers have made potatoes one of their top organic purchases among fresh vegetables even though organic potatoes carry a price significantly higher than most other vegetables [40].…”
Section: Introductionmentioning
confidence: 99%
“…When all the varieties were compared there was a significant difference (p˂ 0.05) observed in their TP levels especially between the fresh and the freeze dried variety. The highest levels of TP were consistently found in extractions of freeze dries blueberries [32].…”
Section: Resultsmentioning
confidence: 90%